1983
DOI: 10.1111/j.1399-0039.1983.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR antigens and properdin factor B allotypes in responders and non‐responders to the Rhesus‐D antigen

Abstract: HLA‐DRw6 incidence was high in male responders to the Rhesus‐D antigen (50%) compared to male non‐responders (15.4%), P>0.02, P corrected N/S, pregnancy immunized females (23.1%) and a random population (26%). No Bf allotype frequency differences were found among these four groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…A general analysis of this population according to sex indicated that women were more likely to produce red cell antibody than men (63% of women vs 46% of men). Similar increased immune responsiveness in women had been seen in the National Sickle Cell program and in other studies (Orlina et al 1978, Dutcher et al 1981, Darke et al 1983). Analysis of data with distinction between multiparous and nulliparous women ( Table 2) indicated that nulliparous females showed a greater level of red cell antibody formation at all levels of transfusion than either males or parous females (p = 0.012 and p = 0.010, respectively).…”
Section: Effect Of Transfusion and Sexlparity On Antibody Responsessupporting
confidence: 78%
See 1 more Smart Citation
“…A general analysis of this population according to sex indicated that women were more likely to produce red cell antibody than men (63% of women vs 46% of men). Similar increased immune responsiveness in women had been seen in the National Sickle Cell program and in other studies (Orlina et al 1978, Dutcher et al 1981, Darke et al 1983). Analysis of data with distinction between multiparous and nulliparous women ( Table 2) indicated that nulliparous females showed a greater level of red cell antibody formation at all levels of transfusion than either males or parous females (p = 0.012 and p = 0.010, respectively).…”
Section: Effect Of Transfusion and Sexlparity On Antibody Responsessupporting
confidence: 78%
“…Although greater innate female responsiveness has been noted by others (Orlina et al 1978, Dutcher et al 1981, Darke et al 1983), the distinction between nulliparous and multiparous females was surprising. We feel that the apparently increased risk for red cell sensitization in nulliparous females in this study should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 83%
“…Numerous studies attempted to determine MHC determinants for anti‐D immunization and higher frequencies as well as frequencies equal to controls of DRB1*15 and DQB1*02 (genetically linked to DRB1*03) alleles were reported 1,20‐22. In our study, anti‐D was predominantly pregnancy induced and single D antibodies were associated with DRB1*01 and DRB1*11 and less strongly with DRB1*03 while a DRB1*15 association was only found in multiple specificity responders, with or without anti‐D.…”
Section: Discussionmentioning
confidence: 50%
“…First et al (1977) reported the hyperacute rejection of renal allografts in man due to those cross-reacting antibodies against streptococci. Darke et al (1983) reported ii significant correlation between DRw6 and the immune response to the Rhesus-D antigen in males. Wojtulewicz-Kurkus et al (1981) reported that among a group of individuals who were deliberately immunized against Rhesus-D. all of the DRw6 positive ones belong to the responder group.…”
Section: Hla-drw6 As a Marker For Immune Responsivenessmentioning
confidence: 96%